EFEKTIVITAS PELAKSANAAN SERTIFIKASI KEANDALAN WEBSITE JUAL BELI ONLINE DALAM MENANGGULANGI PENIPUAN KONSUMEN - Eka Nugraha Putra; Wika Yudha Shanty; Hatarto Pakpahan (University of Merdeka Malang, 2017)
When electronic transactions often consumers are required to enter some personal data in electronic systems. Personal data held by consumers is abused by business actors when consumers enter their personal data first in the online trading website. The sale of personal data to other companies or product offerings that violate the rights of consumers may result from a black of protection or a security guarantee of personal data from consumers entered on the online buying and selling website. This problem also arises because of the consumer’s perspective on the awareness of their Inadequate rights and the need for stricter consumer protection law enforcement, particularly in online transactions. This factor causes quite a number of cases related to online consumer fraud, where although it is regulated but the government has not provided a definite form of legal order to provide protection to consumers. This study examines and analyzes the rules regarding certification of reliability in legislation and constraints in its implementation, as well as how the ideal arrangement relates to the implementation of website reliability certification. DOI: https://doi.org/10.26905/idjch.v8i2.1674